Pengaruh Tabungan Mudharabah, Deposito Mudharabah Terhadap Pembiayaan Mudharabah Pada BPRS Di Indonesia Priode 2019-2022 - Apriani, Nurul; Hasan, Asyari (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine how the influence of Mudharabah Savings, Mudharabah Deposits on Mudharabah Financing at BPRS in Indonesia for the period 2019-2022. This research uses quantitative research methods. The results of the study were tested with multiple linear regression using the IBM SPSS_24 programme, while the data collection of BPRS in Indonesia for the 2019-2022 period was directly obtained after conducting research on BPRS in Indonesia for the 2019-2022 period. The sample technique in this study is to use saturated sampling or total sample, namely sampling when all populations are used as samples. Based on the t-test test that the Mudharabah Savings variable (X1) has a tcount value < ttable (10.789 < 2.201), and the Mudharabah Deposit variable (X2) has a tcount value> ttable (1.435 > 2.201), this proves that there is no effect of Mudharabah Savings (X1) on the increase in Mudharabah Financing at BPRS in Indonesia priode 2019-2022 persially while the Mudharabah Deposit variable (X2) has an influence on Mudharabah Financing at BPRS in Indonesia priode 2019-2022. And based on the results of the F-test data analysis shows that simultaneously or together the Mudharabah Savings (X1) and Mudharabah Deposit (X2) variables simultaneously affect Mudharabah Financing (Y), where the sig value is 0.158